2003
DOI: 10.1194/jlr.m300180-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

Phosphatidylcholine-enriched diet prevents gallstone formation in mice susceptible to cholelithiasis

Abstract: Cholesterol gallstones affect approximately 10-15% of the adult population in North America. Phosphatidylcholine (PC) is considered to be the main cholesterol solubilizer in bile. This study examined the effect of a PCenriched diet on gallstone incidence in mice susceptible to cholelithiasis. The result obtained showed that the feeding of a lithogenic (LG) diet for 4 weeks or 8 weeks resulted in cholesterol gallstone incidences of 47% and 89%, respectively. These gallstone incidences were either reduced or pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 44 publications
1
9
0
1
Order By: Relevance
“…Cholelithiasis, which is considered as a common disease in the clinic, is caused by several factors like metabolic abnormalities and lifestyle habits and it usually consists of cholesterol and pigments. 1,2 According to the site of lithiasis, cholelithiasis is mainly divided into cholecystolithiasis, hepatolithiasis, and extrahepatic bile duct stones. Cholelithiasis is known as one of the most prevalent surgical ailments that clinical surgeons encounter during clinical practice; about 10%–15% of adults suffer from cholelithiasis in the United States.…”
Section: Introductionmentioning
confidence: 99%
“…Cholelithiasis, which is considered as a common disease in the clinic, is caused by several factors like metabolic abnormalities and lifestyle habits and it usually consists of cholesterol and pigments. 1,2 According to the site of lithiasis, cholelithiasis is mainly divided into cholecystolithiasis, hepatolithiasis, and extrahepatic bile duct stones. Cholelithiasis is known as one of the most prevalent surgical ailments that clinical surgeons encounter during clinical practice; about 10%–15% of adults suffer from cholelithiasis in the United States.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, an increase in the total concentration of L in supersaturated bile might decrease the ChA T value to~1.05, as the TC/L = 2.0 system, and prevented the Ch nucleation regardless of the presence of calcium ions. This implies that, under an increase in L secretion for the supersaturated bile, Ch gallstones may not be formed, [38] similar to the administration of ursodiol for the prevention of Ch gallstones. [42][43][44] For bile containing rich amount of L, the activity of calcium at high L concentration was slightly lower than that at low L concentration.…”
Section: Discussionmentioning
confidence: 99%
“…[5,6,36,37] On the other hand, humans in healthy condition and under phosphatidylcholine-enriched diet or chenodiol administration, an increase in L secretion and a decrease in Ch secretion in the bile might greatly cause a high Ch solubility (i.e., a low CSI), in contrast to increase in the L secretion only for choline-enriched diet. [10,38,39] More evidences showed that the administration of soy L had significantly reduced the absorption of Ch for hypercholesterolemic patients. [40,41] Therefore, a low ChA T (~1.05) bile similar to the supersaturated TC/L = 2.0 and CSI < 1.5 system was formed.…”
Section: 7 | Prevention Of Gallstone Formationmentioning
confidence: 99%
“…In a clinical study, biliary cholesterol crystallization or lipid solubilization did not change with dietary modification [49]. On the other hand, a recent study by the group of Yousef [50] has shown that feeding PC-enriched diet (2% or 6% PC), cholesterol gallstone formation was reduced or prevented in cholesterol gallstone susceptible mice fed a lithogenic diet. Interestingly, although no changes in net biliary secretion of PC were observed in those mice, PC-enriched diet resulted in increased bile flow and one-phase micellar zone of the ternary phase diagram with subsequent decrease in cholesterol saturation index.…”
Section: Phospholipidsmentioning
confidence: 96%